Thromboelastography parameters in chronic viral liver disease and liver resection: a retrospective study - Ying Di; Jialu Li; Chunjuan Ye; Zheng Wang; Qianqian Zhu (Singapore Medical Journal)
Introduction: Thromboelastography (TEG) provides a global assessment of haemostasis and is potentially applicable to liver disease. The present study aimed to explore the utility of TEG for the evaluation of patients with chronic viral liver disease, which has previously not been investigated. Methods: Demographic characteristics and TEG parameters were collected before surgery. Child–Turcotte–Pugh (CTP) and model for end-stage liver disease (MELD) scores were used to categorise stages of liver cirrhosis. Liver resections were classified as low, medium and high complexity. Results: A total of 344 patients were included. Results showed significantly longer K-time, smaller α-angle and lower maximum amplitude (MA) with increasing liver disease severity as measured by the CTP and MELD scores (P < 0.05 for all). After multivariable adjustment (including age, sex, liver disease aetiology, alanine aminotransferase [ALT], aspartate aminotransferase [AST], albumin, total bilirubin, haemoglobin and platelet count), TEG parameters (except R-times) were either weakly or inversely related to the severity of liver disease as defined by the MELD score (absolute r < 0.2 and P < 0.05 for all except R-times). R-times obtained before surgery were weakly correlated with perioperative blood loss (r < 0.2 and P < 0.05 for all). Conclusions: The correlation between TEG parameters and severity of liver disease was weak. In addition, R-times obtained before liver resection were weakly associated with perioperative blood loss after multivariable adjustments. TEG utility for haemostasis assessment and prediction of blood loss during liver resection should be further explored in high-quality studies.